Nocardia veterana endogenous endophthalmitis in a cardiac transplant patient - Scott, Megan (Springer, 2013)
BACKGROUND: Endogenous endophthalmitis secondary to Nocardia species is extremely rare but often portends a poor visual prognosis often owing to the advanced nature of disease at presentation and delay in diagnosis. Patients who are systemically immunosuppressed are at greatest risk and early suspicion of the role of this organism in patients with acute panuveitis is paramount. FINDINGS: A 66-year-old cardiac transplant patient on oral prednisone, Myfortic, and tacrolimus developed unilateral panuveitis with a focal white subretinal and retinal lesion. His past medical history was notable for Aspergillus pneumonia and cytomegalovirus retinitis in the contralateral eye 12 months prior. Aqueous humor sampling for eubacterial, eufungal, and viral PCR testing, as well as vitreous cultures for bacteria and fungi were unsuccessful in the identification of a causative organism. Progressive enlargement of the lesion was noted despite intravitreal foscarnet, vancomycin, ceftazidime, and voriconazole. A pars plana vitrectomy and retinal and subretinal biopsy led to the identification of Nocardia veterana, a recently identified Nocardia species. A combination of linezolid, meropenem, azithromycin, ceftriaxone, and intravitreal amikacin resulted in eradication of the infection. CONCLUSION: This is the first reported case of N. veterana endogenous endophthalmitis in an immunosuppressed patient. Pars plana vitrectomy with a subretinal biopsy was required to establish a diagnosis, as other testing including aqueous PCR and vitreous cultures were negative. The poor visual outcome in our patient highlights the importance of early consideration of Nocardia in the differential diagnosis of panuveitis with subretinal disease in the context of immunosuppression.